GHQ-12 in adolescents: contributions to the controversial factorial validity - Pedrero Pérez, Eduardo J.; Mora-Rodríguez, Carlos; Rodríguez Gómez, Rosana; Benítez-Robredo, María Teresa; Ordóñez-Franco, Ana; González-Robledo, Lidio; Méndez-Gago, Susana (Anales de Psicología / Annals of Psychology, 2020)
Objective: The GHQ-12 is one of the most widely used questionnaires in the adult population, but there are not as many studies exploring its applicability in adolescents. The main problem is the diversity of results on its factorial structure, as different studies have shown one, two or three dimensions. The purpose of this study was to explore the GHQ-12 factorial structure for adolescents. Method: An observational multicenter cross-sectional descriptive study was designed for schools in the city of Madrid. A random sample of n=2,171, 14-16-year-olds was stratified by the school’s development level and funding (public, private or mixed). Unrestricted factor analysis was applied based on the polychoric or tetrachoric correlations matrix (depending on the test scoring method). Results: The optimized parallel analysis provided an unequivocal one-factor structure, confirmed by unidimensionality assessment. Around 30% of male and 42% of female adolescents were found to be at risk of developing mental health problems. Conclusions: The GHQ-12 is a one-dimensional test for screening psychological distress, with excellent psychometric properties for its application in an adolescent population. The use of adequate statistical methods can overcome old controversies and promote proper application and interpretation of the results provided by the test.